2006
DOI: 10.1080/00365520600575720
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-dose warfarin and regional chemotherapy on survival in patients with pancreatic carcinoma

Abstract: Treatment with low-dose warfarin improved survival irrespective of the chemotherapy received. Of the regimens examined, the combination of regional gemcitabine and mitomycin-C with systemic gemcitabine was associated with the longest survival time. Survival was increased further by the addition of warfarin. These data provide a rationale, based on safety and efficacy, for a definitive study on the use of warfarin and combined regional and systemic chemotherapy in patients with pancreatic carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 33 publications
1
16
1
1
Order By: Relevance
“…Nakchbandi et al [25], however, in their retrospective study of patients with pancreatic cancer, found a significant effect on survival among those taking very low dose of warfarin, thus providing recent confirmation of our own findings.…”
Section: Discussionsupporting
confidence: 83%
“…Nakchbandi et al [25], however, in their retrospective study of patients with pancreatic cancer, found a significant effect on survival among those taking very low dose of warfarin, thus providing recent confirmation of our own findings.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, in a large population-based study, longterm treatment with vitamin K antagonists was associated with reduced risk for cancer development, especially prostate cancer (37 ). Substantiating this, Nakchbandi et al reported that low doses of the vitamin K antagonist warfarin increased survival of patients with pancreatic carcinoma (38 ). However, it is thus far unclear whether these effects depend solely on flTF-mediated processes.…”
Section: Therapeutic Implications Of Targeting Tfmentioning
confidence: 97%
“…Three studies also included adjuncts to chemotherapy: warfarin, angiotensin-II, and degradable starch microspheres. [26, 28, 37]…”
Section: Methodsmentioning
confidence: 99%